Tree species composition for squirrel-observation recreational activity in botanical garden, Putrajaya / Noraini Bahari, Ismail Said and Noradila Rusli - Noraini, Bahari; Ismail, Said; Noradila, Rusli (Universiti Teknologi MARA, Perak, 2018)
Squirrel is one of the important natural components in urban ecosystems. It commonly inhabits urban parks in many cities of Peninsular Malaysia. The understanding of how they use trees is essential in creating wildlife habitats for supporting wildlife-oriented recreational activities in urban parks. Direct observation through focal animal sampling was employed in order to understand the tree composition which influences squirrel’s behaviours in Botanical Garden, Putrajaya. The result shows that squirrels mainly forage and feed in fruits and flowers bearing trees. Inasmuch, this paper suggests the tree species composition which is suitable for squirrel’s habitat in urban parks